INFLUENCE OF NEUROMUSCULAR ELECTRICAL STIMULATION AND KINESIOTHERAPY IN THE RANGE OF MOTION OF THE HANDLE OF HEMIPARETIC SUBJECTS - Souza, Juliana de Oliveira; Silva, Suelen de Almeida; Januário, Priscila de Oliveira; Cruz, Ariela Torres (Journal of Health Care, 2015)
Introduction: The stroke is considered the main neurological impairment that causes disability amongadults. The hemiparesis is a common motor dysfunction among individuals who have suffered stroke.Neuromuscular Electrical Stimulation (NMES) and kinesiotherapy are resources used in the treatmentof these individuals. Objectives: To investigate the influence of NMES with or without cinesiotherapyin range of motion (ROM) in flexion and extension active of wrists in patients with stroke sequelae.Materials and methods: Eighteen patients were divided into two groups: one was treated NMES theother one with NMES associated with kinesiotherapy, both groups were subject of 16 attendances, beingevaluated before, at the end of treatment and after one and three months after completing the treatment.Results: There was an increase in flexion and wrist extension in both groups within three months aftercompleting the treatment. However, it was found that to increase the extension ROM, the treatment withNMES associated with kinesiotherapy was more effective when compared to the use of NMEE in isolation.Conclusions: These proposed treatments were able to provide increased flexion and wrist extensionof the studied population, however, the treatment with the NMEE associated with kinesiotherapy wasmore effective for increasing the extension ROM.
Keywords: Stroke; hemiparesis; electrical stimulation; kinesiotherapy; joint goniometry.